Penerapan Metode Waspas Dalam Penilaian Kinerja Guru Terbaik - Waruwu, Desmi; Dianti, Selvia Rama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
An analytical approach called teacher performance appraisal is used to provide better teaching instruction. At SD Negeri 101778, the teacher assessment method is less detailed. It is feared that the assessment, which is still insignificant and based on personal interests, will be subjective and cause social jealousy among teachers who have not yet received a recommendation. Weighted Aggregated Sum Product Assessment). In the process of ranking the performance of the best teachers, you can use the WASPAS method with predetermined criteria. The final results of this study show that alternative data A2 gets the highest score with a score of 1,962, so Alternative A2 has the best teacher performance